Theologian, mathematician and storyteller (2017)
Eduardo Saénz is a man who life was leading to scientific dissemination. From telling stories in his city, he went on to tell them in a contest, then at TED, then in his book Mathematical Intelligence and has no longer stopped touring the world telling science in an entertaining way for all.